1998
DOI: 10.1177/074171369804800402
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Myth of Self-Actualization: Reinventing the Community Perspective of Adult Education

Abstract: In this contribution, we discuss two tendencies in mainstream adult and continuing education. First, there is the tendency to gear adult and continuing education towards individualized responses to present day processes of social transformation. We interpret these changes with reference to the concept of the risk society. Second, we comment on the tendency of adult and continuing eduction to increasingly frame these individualized responses in labor market terms. These tendencies provoke a privatization of ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The process and journey toward 'community actualization' within healthcare and HPE environments, as opposed to only forms of individualistic 'self-actualization' processes that commonly drive current knowledge and skill attainment (Jansen and Wildemeersch 1998), will need to include Indigenous-led permeation of important traditional knowledges and concepts. Respect, Relevance, Reciprocity, and Responsibility are key tenets of Indigenous ways of knowing (Kirkness and Barnhardt 1991) that are applicable to the operationalization of value-based environmental stewardship and sustainability actualization processes that are predicated on goals for healthy people, community, and planet.…”
Section: The Way Forwardmentioning
confidence: 99%
“…The process and journey toward 'community actualization' within healthcare and HPE environments, as opposed to only forms of individualistic 'self-actualization' processes that commonly drive current knowledge and skill attainment (Jansen and Wildemeersch 1998), will need to include Indigenous-led permeation of important traditional knowledges and concepts. Respect, Relevance, Reciprocity, and Responsibility are key tenets of Indigenous ways of knowing (Kirkness and Barnhardt 1991) that are applicable to the operationalization of value-based environmental stewardship and sustainability actualization processes that are predicated on goals for healthy people, community, and planet.…”
Section: The Way Forwardmentioning
confidence: 99%
“…On account of the unscientific nature of his work, Maslow came in for considerable criticism from established science: most of his work is phenomenological-based on his personal experiences in working with people, and not on systematic empirical research. Others later pointed out that Maslow's views were keyed to the individual, and that he devoted much less attention to the social environment within which a person develops (Jansen and Wildemeersch, 1998). Maslow himself was the first to admit that a great deal of research was still needed to support and supplement his observations (for that is what they were, not fabrications): 'I have found that it helps to remove scientific uneasiness about my freewheeling explorations, affirmations, and hypotheses if I am willing to call them prescientific rather than scientific, a word which for so many means verification rather than discovery' (Maslow, 1971: 286).…”
Section: Peak and Plateau Experiencesmentioning
confidence: 99%
“…He concludes that unfortunately a detailed analysis of continuing vocational training structures and developments in Europe is hampered by a considerable lack of data. Jansen and Wildemeersch (1998) point out that the concept of qualification predominates, with its implication of the practical usefulness of knowledge, skills and attitudes in situations of daily work and life, and has become a general standard with which to measure the meaning and significance of educational activities. This is in contrast to connecting the perspective of social integration with the self-actualization of the individual.…”
Section: For M S Of Decentr a Liza Tionmentioning
confidence: 99%